UMPSA signs memorandum of understanding with COHU Malaysia to strengthen industry-academia collaboration - Naqiah, Puaad (UMPSA, 2025)
AYER KEROH, MELAKA, 18 August 2025 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) continues to strengthen its strategic collaboration network with the signing ceremony of a Memorandum of Understanding (MoU) with COHU Malaysia Sdn. Bhd. held at Ayer Keroh, Melaka.